2013
DOI: 10.2134/jeq2012.0266
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Retention in a Newly Constructed Wetland Receiving Agricultural Tile Drainage Water

Abstract: One measure used in Sweden to mitigate eutrophication of waters is the construction of small wetlands (free water surface wetland for phosphorus retention [P wetlands]) to trap particulate phosphorus (PP) transported in ditches and streams. Th is study evaluated P retention dynamics in a newly constructed P wetland serving a 26-ha agricultural catchment with clay soil. Flow-proportional composite water samples were collected at the wetland inlet and outlet over 2 yr (2010)(2011) and analyzed for total P (TP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 30 publications
6
28
0
Order By: Relevance
“…In the ICECREAM model, different P fraction concentrations (both dissolved and particulate P) are calculated and the proportion of dissolved P (DP) varied from 21% in Eks to 44% in Wig. In Ber, the mean modeled DP concentration accounted for 39% of TP, which is in accordance with results from a water quality study presented by Kynkäänniemi et al (2013). Their results showed that on an annual basis, DP constituted approximately one third of TP.…”
Section: Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…In the ICECREAM model, different P fraction concentrations (both dissolved and particulate P) are calculated and the proportion of dissolved P (DP) varied from 21% in Eks to 44% in Wig. In Ber, the mean modeled DP concentration accounted for 39% of TP, which is in accordance with results from a water quality study presented by Kynkäänniemi et al (2013). Their results showed that on an annual basis, DP constituted approximately one third of TP.…”
Section: Tablesupporting
confidence: 88%
“…Two of the wetlands, Ber and Ski, were both designed with a shallow section covered with emergent plants following an open water inlet section. Ber consisted of a 1 m deep sedimentation pond followed by a 0.3 m deep section with emergent plants (Kynkäänniemi et al, 2013). In Ski, the shallow (0.2-0.3 m) section was placed between two deeper (approximately 1.2 m) sections (Fig.…”
Section: Wetland Descriptionsmentioning
confidence: 99%
“…Dividing the volume treated (27, Overall, the performance of the IESF in this study (63.9% phosphate and 66.3% total phosphorus load reduction) is comparable to other agricultural treatment practices and studies of IESFs. The IESF captures more phosphorus than constructed wetlands, for both total phosphorus (2-44%, [10][11][12][13][14]) and phosphate (9%, [12]), though the data falls within the upper range reported for a study of 17 intensively studied constructed wetlands (TP = 1-88%; DRP = −19 to 89%, [15]). Laboratory experiments of IESFs in previous studies found an average of 88% phosphate capture with a total treated depth of 200 m [18].…”
Section: Hydraulic and Phosphate Loading Ratesupporting
confidence: 46%
“…Sediments having high Al, Fe, and organic matter contents are favor of accumulating legacy P pools since flooding promotes the P adsorption by created noncrystalline forms of Fe, Al, and organic matter (Ardón et al, 2010). In terms of geographical location, standing waters that located closer to the source (e.g., croplands and wastewater discharge) can more substantially retain nutrients (Kynk€ a€ anniemi et al, 2013). In shallow and productive waters, P accumulation rate can be enhanced by increasing of dissolved oxygen at the sediment surface in response to fluctuating water levels and vegetation growth cycles (e.g., summer) or by receiving Fe and Al loads from entered runoff (Reddy and DeLaune, 2008).…”
Section: Legacy Nutrient Dynamics In Sedimentsmentioning
confidence: 99%